Analysis of Academic Information System Using Information System Success Model and System Quality Model Case Study of Institut Teknologi Nasional Malang - Kurnia Dwi setyowati; Totok Chamidy; Muhammad Faisal (Transactions on Informatics and Data Science, 2024)
Advancements in information technology are progressing rapidly, providing numerous conveniences across various domains, ranging from personal needs to general activities. Academic Information System (SIAKAD) facilitates academic information management in educational institutions. The utilization of website-based SIAKAD is gaining popularity due to its ability to streamline access to information and minimize administrative errors. This Research aims to identify key factors contributing to the success of website-based SIAKAD at the National Institute of Technology Malang. Additionally, the Research seeks to assess the level of success of SIAKAD and evaluate the key factors that influence its success. This Research employed the Information System Success Model (ISSM) method and the System Quality Model (SQM). This study follows a seven-step workflow, from problem identification to conclusion, assessing SIAKAD ITN Malang's success using ISSM and SQM models. A survey of 100 respondents evaluated system quality, functionality, and user satisfaction. Related research highlights the importance of system quality in achieving positive user outcomes and overall success. Based on the research results, all hypotheses are accepted, indicating that Information Quality (IQ), System Quality (SQ), and Service Quality (SeQ) significantly influence Intention to Use (IU), User Satisfaction (US), and Net Benefit (NB) in the Use of SIAKAD at the National Institute of Technology Malang.